(3LQjeI GdRfi (B:s (3aj GdbGfhf GdeUQj hGdebGQf (B/ s - (3CMeO MGaX fhQs; (3eMehO eMehO eUWais; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 1958)
(3OQGSI dLQjeI GdRfG ef MjK GNJdGagG aj GdReGf hGdecGf hGdehVhY hGdGLQGAGJ GdJj jdbGgG cd ef SGge ajgG ShGA CcGfJ aGYdG Ch TQjcG (B, (3hMUQ GdYjhH GdJj JQO aj GdfUhU GdhVYjI aj YTQI YjhH CgegG (B: (3Ef GdQLd aj Md ef Cf jNhf RhLJg aj Cj ecGf TGA YOG efRd GdRhLjI (B, (3hefgG GYJHGQ GdRhL hMOg Yjf eaGLFI dRhLJg (B,(3bHdI ddLQjeI jJeJY HYPQ eNaa dLfGjI bJdg hGjGgG (B, (3hgj hLhHj ddbGVj (B, (3hJbJQM GdQSGdI Cf jJeJY HGdYPQ GdeNaa CHhgG Ch CNhgG (B,(3hGdRhLI faSgG hJfU Ydj Gf KHGJ GdLQjeI jchf HWQjbI ef WQb GdGbfGY eGYOG TQjc GdRhLI (B,(3ajdRe ddEKHGJ Ydjg hLhO aj efRd eSde HGdeMd GdeNUU ddLQjeI (B, (3hGdJdHjS Ch GdEYJQGa Bh hLhO ecGJH (B. (3Ch ChQGb UGOQI efgG (B, (3hYjH efM GdRhL Ohf GdRhLI Mb GdGYaG Yf GdRhLI GdeMche YdjgG fgGFiG hENQGLgG ef GdSLf (B, (3hYjH YbGH GdRhLI GdRGfjI aj Cj ecGf HGdMHS GdPj jUd Gdj SfJHjf hYdj GdRhL GdRGfj GdMHS GdPj dGjJYOj SJI CTgQ (B, (3hbO aGJ GdeTQY aQUI OQGSI Cf jehJ GdRhL hgh jMGhd bJd GdRhLI GdeJdHSI HaYd OaGYgG Ch TQjcgG (B, (3Yf GdfaS (B, (3GP ef SjJbOe HGdTchj VOgG (B, (3hJQj Cf jDhd gPG GdMb ddfjGHI Ch CbQH GaQGO GSQJg Gdjgs
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFj, (B1958.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdLRGA GdLfGFjs; (3GdLRGA GdeOfjs; (3GdbGfhf GdeUQjs; (3GdTQjYI GdESdGejIs; (3GdGTJQGc aj GdRfis; (3OYhi GdRfis; (3GdbGfhf GdghdfOjs; (3GdbGfhf GdgfOjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs